An Australian study comparing the use of multiple-choice questionnaires with assignments as interim, summative law school assessment. Issue 4 (19th May 2017) - Huang, Vicki
Abstract : To the author's knowledge, this is the first Australian study to empirically compare the use of a multiple-choice questionnaire (MCQ) with the use of a written assignment for interim, summative law school assessment. This study also surveyed the same student sample as to what types of assessments are preferred and why. In total, 182 undergraduate property law students participated in this study. Results showed that scores for the MCQ (assessing five topics) and assignment (assessing one topic) followed a similar distribution. This indicates that an MCQ does not necessarily skew students towards higher grades than an assignment. Results also showed significant but low correlations of test scores across instruments. When asked which instrument best assessed their knowledge of property law, students expressed a strong preference for an assignment over an MCQ or examination. Comments revealed a strong belief that, because lawyers write, law schools must assess legal writing – a skill not captured by MCQs. This study is important as many Australian law schools face increasing marking loads due to higher student numbers and compulsory mid-term assessments. This article endorses the use of MCQs but only as part of a diverse suite of law school assessment.